Evaluation of a Small Inland Ferry’s Energy Requirements from the Acceleration Stage of Towing Tank Model Tests - Kunicka Magdalena; Wrzask Klaudia; Litwin Wojciech; Grygorowicz Mirosław; Zeratgaar Hamid (Polish Maritime Research)
Computing the power required to meet a ship’s operational needs is one of the most important tasks in naval design. The power required to propel a vessel is directly related to the resistance the hull experiences as it moves through the water. The conventional method of determining a ship’s resistance involves towing tank tests of ship models at a fixed speed; however, for short-range vessels, where constant speed is not the primary mode of operation, a dynamic model is needed. This paper demonstrates a way in which different operational motion profile models can be retrieved from the acceleration stage of towing tank tests. We show that the data from the acceleration stage, often overlooked in towing tank tests, allow us to derive the gliding equations of motion. A dynamic model of a small inland ferry on the Motława River in the city of Gdańsk is developed, which enables optimisation of the required power based on different operation profiles.